Congenital Muscular Torticollis: A Diagnosis in Adult Age - Joana, Miguel; Departamento de Medicina Física e de Reabilitação, Centro Hospitalar Entre o Douro e Vouga (CHEDV). Santa Maria da Feira, Portugal (2021)
A 21 years old female patient was referred due to pain and slight functional limitation of the left shoulder. There was fibrous band swelling of the left sternocleidomastoid muscle’s clavicular head. The imaging study revealed enlargement of the inner half of the left clavicle and diffuse thickening of the clavicular head of the left sternocleidomastoid muscle, suggesting fibrosis. After surgery, another rehabilitation program was initiated and the patient had a good recovery.